93.9k views
1 vote
F={(-2,-1), (2,-2),(-1,4)}g={(4,-3),(-5,1),(-2,-4)}(fg)(-2)=

User Stonecraft
by
5.8k points

1 Answer

5 votes

The function composition is defined as shown below


(f\circ g)(x)=f(g(x))

Thus,


(f\circ g)(-2)=f(g(-2))=f(-4)

And we cannot completely calculate (f∘g)(-2) since we are missing the value of f(-4).

On the other hand, we can calculate the product (fg)(-2) as shown below.


(fg)(x)=f(x)g(x)

Then,


\begin{gathered} (fg)(-2)=f(-2)g(-2)=-1\cdot-4=4 \\ \Rightarrow(fg)(-2)=4 \end{gathered}

The result of the product of functions (fg)(-2) is 4.

User Abbos Tajimov
by
5.0k points